Екзистенціальні аспекти самоздійснення в контексті сучасного розмаїття медіа - Доброносова, Ю. Д.; Dobronosova, Yu. D. (My University, 2017)
У статті окреслюється розуміння медіадосвіду й медіальності як виявів екзистенціальної специфіки людського існування та обговорюється специфіка екзистенціальних аспектів самоздійснення в контексті сучасного розмаїття медіа. Підкреслено, що неінструментальне розуміння всіх поколінь медіа допомагає розвивати філософію медіа як сучасну філософську антропологію. Мас-медіа й нові цифрові медіа представлено як креативний ресурс сучасної медіакультури. Нові медіа є мультимедійними та поліфункціональними, нині медіадосвід перетворюється на екзистенціальний досвід, проте всі медіа як неоднозначний феномен мають неоднозначний потенціал. Автор стверджує, що сучасне медіарозмаїття є екзистенціальним викликом, тому що нові медіа є екзистенціальними посередниками й онтологічними машинами-апаратами, котрі впливають на формування орієнтирів існування сучасної людини.

В статье очерчивается понимание медиаопыта и медиальности как проявлений экзистенциальной специфики человеческого существования и обсуждается специфика экзистенциальных аспектов самоосуществления в контексте современного разнообразия медиа. Подчеркивается, что неинструментальное понимание всех поколений медиа помогает развивать философию медиа как современную философскую антропологию. Мас-медиа и новые цифровые медиа представлены как креативный ресурс современной медиакультуры. Новые медиа мультимедийны и полифункциональны, ныне медиаопыт превращается в экзистенциальный опыт, однако все медиа являются неоднозначным феноменом и имеют неоднозначный потенциал. Автор утверждает, что современное медиаразнообразие является экзистенциальным вызовом, поэтому новые медиа – экзистенциальные посредники и онтологические машины-аппараты, которые влияют на формирование ориентиров существования современного человека.

The article defines meaning of mediaexperience and mediality as manifestations of existential specific human existence and discusses the specifics of existential aspects of self-realization in the modern media variety context. Author highlights that the uninstrumental understanding of the all generations of media can help to develop the philosophy of media as a modern philosophical anthropology. Mass-media and new digital media is presented as a creative resource of modern media culture. New media are multimedial and multifunctional, now media ex- perience becomes the existential experience, but all media as a ambivalent phenomenon has ambivalent existential potential. Author argues that modern media variety is an existential challenge, because new media are existential mediators ontological machines-devices that influence the formation of guidelines existence of modern man.

The article defines meaning of mediaexperience and mediality as manifestations of existential specific human existence and discusses the specifics of existential aspects of self-realization in the modern media variety context. Author highlights that the uninstrumental understanding of the all generations of media can help to develop the philosophy of media as a modern philosophical anthropology. Mass-media and new digital media is presented as a creative resource of modern media culture. New media are multimedial and multifunctional, now media ex- perience becomes the existential experience, but all media as a ambivalent phenomenon has ambivalent existential potential. Author argues that modern media variety is an existential challenge, because new media are existential mediators ontological machines-devices that influence the formation of guidelines existence of modern man.
Доброносова Ю. Д. Екзистенціальні аспекти самоздійснення в контексті сучасного розмаїття медіа / Ю. Д. Доброносова // Актуальні проблеми філософії та соціології: Науково-практичний журнал / Голов. ред. Д. В. Яковлев; відпов. секретар І. В. Шамша; Міністерство освіти і науки України; Національний університет "Одеська юридична академія". - Одеса, 2017. - Вип. 16. - С. 29-32.
Keywords: медіарозмаїття; медіадосвід; нові медіа; екзистенціальне самоздійснення; медіальність; медиаразнообразие; медиаопыт; новые медиа; экзистенциальное самоосуществление; медиальность; media variety; media experience; new media; existential self-realization; mediality